Remote Cerebellar Haemorrhage after Surgery for Craniopharyngioma: a case report - Bishokarma, Suresh; Shrestha, Shikher; Devkota, Upendra Prasad (Nepal Journal of Neuroscience, 2018)
Postoperative remote cerebellar haemorrhage occurring distant to the operated site as its name suggests is a rare though recognized entity in neurosurgical practice. It can be potentially devastating. Over 100 cases have been described in various literatures over the years. It is postulated to be due to CSF over drainage, has been the most popular theory behind its occurrence. We report a patient who underwent pterional craniotomy for craniopharyngioma, who deteriorated 12 hours following awakening after the surgery, the cause being remote cerebellar haemorrhage. Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, Page: 45-48